Decaffeinated coffee and its benefits on health: focus on systemic disorders. Issue 15 (22nd August 2021) - Colombo, Raffaella; Papetti, Adele
Abstract: The current literature has mainly focused on benefits and risks deriving from the consumption of caffeinated coffee and its implications for inflammation, cardiovascular diseases, neurodegenerative disorders, and cancer. Today, data about the role of caffeine in many disorders are controversial and the attention has increasingly focused on decaffeinated coffee and its non-caffeine compounds, which could have mainly beneficial effects. In fact, coffee phenolic compounds not only exhibit well-known antioxidant properties, but they can also antagonize some negative effects of caffeine, for example in inflammatory pathway and in glucose metabolism and homeostasis. In this review, we consider the literature of the last two decades and critically discuss the effects of decaffeinated coffee compounds on systemic disorders, mainly inflammation, cardiovascular diseases, hepatic dysfunctions, and cancer.